WIDTH AND THICKNESS OF FLUVIAL CHANNEL BODIES AND VALLEY FILLS IN THE GEOLOGICAL RECORD: A LITERATURE COMPILATION AND CLASSIFICATION - Gibling M.R. (My University, 2006)
The three-dimensional geometry of fluvial channel bodies and valley fills has received much less attention than their internal structure, despite the fact that many subsurface analyses draw upon the geometry of suitable fluvial analogues. Although channel-body geometry has been widely linked to base-level change and accommodation, few studies have evaluated the influence of local geomorphic controls. To remedy these deficiencies, we review the terminology for describing channel-body geometry, and present a literature dataset that represents more than 1500 bedrock and Quaternary fluvial bodies for which width (W) and thickness (T) are recorded. Twelve types of channel bodies and valley fills are distinguished based on their geomorphic setting, geometry, and internal structure, and log-log plots of W against T are presented for each type. Narrow and broad ribbons (W/T < 5 and 5-15, respectively) and narrow, broad, and very broad sheets (W/T 15-100, 100-1000, and > 1000, respectively) are distinguished. The dataset allows an informed selection of analogues for subsurface applications, and spreadsheets and graphs can be downloaded from a data repository. Mobile-channel belts are mainly the deposits of braided and low-sinuosity rivers, which may exceed 1 km in composite thickness and 1300 km in width. Their overwhelming dominance throughout geological time reflects their link to tectonic activity, exhumation events, and high sediment supply. Some deposits that rest on flat-lying bedrock unconformitics cover areas > 70,000 km2. In contrast, meandering river bodies in the river bodies in the dataset are < 38 m thick and < 15 km wide, and the organized flow conditions necessary for their development may have been unusual. They do not appear to have built basin-scale deposits. Fixed channels and poorly channelized systems are divided into distributary systems (channels on megafans, deltas, and distal alluvial fans, and in crevasse systems and avulsion deposits), through-going rivers, and channels in eolian settings. Because width/maximum depth of many modern alluvial channels is between 5 and 15, these bodies probably record an initial aspect ratio followed by modest widening prior to filling or avulsion. The narrow form (W/T typically < 15) commonly reflects bank resistance and rapid filling, although some are associated with base-level rise. Exceptionally narrow bodies (W/T locally < 1) may additionally reflect unusually deep incision, compactional thickering, filling by mass-flow deposits, balanced aggradation of natural levees and channels, thawing of frozen substrates, and channel reoccupation. Valley fills rest on older bedrock or represent a brief hiatus within marine and alluvial successions. Many bedrock valley fills have W/T < 20 due to deep incision along tectonic lineaments and stacking along faults. Within marine and alluvial strata, upper Paleozoic valley fills appear larger than Mesozoic examples, possibly reflecting the influence of large glacioeustatic fluctuations in the Paleozoic. Valley fills in sub-glacial and proglacial settings are relatively narrow (W/T as low as 2.5) due to incision from catastrophic meltwater flows. The overlap in dimensions between channel bodies and valley fills, as identified by the original authors, suggests that many braided and meandering channel bodies in the rock record occupy paleovalleys. Modeling has emphasized the importance of avulsion frequency, sedimentation rate, and the ratio of channel belt and floodplain width in determining channel-body connectedness. Although these controls strongly influence mobile channel belts, they are less effective in fixed-channel systems, for which many database examples testify to the influence of local geomorphic factors that include bank strength and channel aggradation. The dataset contains few examples of highly connected suites of fixed-channel bodies, despite their abundance in many formations. Whereas accommodation is paramount for preservation, its influence is mediated through geomorphic factors, thus complicating inferences about base-level controls. Copyright © 2006, SEPM (Society for Sedimentary Geology).
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная